QuEChERS-based method for pesticides analysis in adipose tissue associated with rat Ovaries - Zamariola, Nathalie [UNESP]; Netto, Pedro Toledo; Franchi, Carla Adriene da Silva [UNESP]; De Camargo, João Lauro Viana [UNESP]; De Marchi, Mary Rosa Rodrigues [UNESP] (Oxford University Press (OUP), 2017)
The concomitant exposure to low doses of various pesticides is one of the most relevant issues in human toxicology today. An experimental toxicology study was developed to evaluate the effects of this type of exposure on the reproductive capacity of females of three species of rats that were exposed to mixtures of dicofol, dieldrin, endosulfan and permethrin at low doses (LOAEL and NOAEL). In this context, we have developed a method for determining pesticides in adipose tissue (0.5 g, 49% lipid) associated with the ovaries, based on the QuEChERS (quick, easy, cheap, effective, rugged and safe) strategy. The method quantification limit (LOQ) was 0.5 mg/kg for dicofol and permethrin, 0.05 mg/kg for endosulfan and dieldrin and 0.2 mg/kg for diclorobenzophenone. Mean recoveries ranged from 75% to 93% with a relative standard deviation <13%. The unspecific selectivity (matrix effect) indicates the mandatory use of analytical curves constructed on the matrix extract. All the analyzed samples (53 adipose tissue associated to ovaries) showed residues of dichlorobenzophenone + dicofol, dieldrin and cis-permethrin while trans-permethrin were detected in 40% of the samples but were below the LOQ. The data indicated the bioaccumulation characteristics of these substances.